Equitable, Not Equal: Perspectives of Community-University Partnerships through the Voices of Community Stakeholders - Lorilee R. Sandmann Ph.D. (Adult Education Research Conference, 2005)
Adult and community development practitioners and scholars are frequently involved in community-university partnerships. A core premise of these partnerships is that university engagement in communities is best done via collaborative, mutually respectful, mutually beneficial partnerships (HUD, 2002). Effective partnerships take time and effort and they require mobilizing resources from diverse parties with overlapping and sometimes conflicting interests. Sustaining them requires that the parties strike a balance between the interest of communities and of higher education institutions.